Escola fundamental de nove anos: em destaque o trabalho do professor do 1º. ano na rede municipal paulistana - Simão, Ana Lucia (2011)
This study aimed to investigate the work of the classroom´s teacher of the current 1st year of the nine years elementary school implemented in accordance with Law No. 11.274/06, which determines the inclusion of six years old children in a nine years term elementary school. We tried to capture the daily activities of the teacher of the six years old children, as well as the organization of the educational work. It is a qualitative research complemented by an analysis of the legislation enforcing the expansion of the term of the elementary school. Instruments were the observation and questionnaires , based in the work of two teachers and first year students in a public school in São Paulo. The theoretical framework was based on the investigative process in Wallon for understanding social interaction in the learning process and development of the child. The data point to a sudden commute of children in early childhood education to the elementary school, marked by the concern of teachers in literacy, but generally there is no understanding by the students in reading and writing. Time and space intended for recreational activities and collectives, were considered inadequate to meet the specifics of the education of children this age group